2022
DOI: 10.1038/d41586-022-00712-4
|View full text |Cite
|
Sign up to set email alerts
|

Africa: sequence 100,000 species to safeguard biodiversity

Abstract: leeper fish (Bostrychus africanus) are a staple food in West Africa. Harvesting them provides an important source of income for hundreds of communities across the Gulf of Guinea in the Atlantic Ocean. Yet little is known about the genetics of this fish -information that is crucial to safeguarding its genetic diversity, and to enhancing its resilience in the face of climate change and other pressures.This situation is all too familiar across Africa. Consider orphan crops, which have a crucial role in regional f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 19 publications
(16 reference statements)
0
48
0
Order By: Relevance
“…Importantly, our project provides a model for increasing the representation of local researchers in the sequencing of their indigenous crops. Recent studies and commentaries have highlighted the disconnect between the species origin and the location of the institutions leading their sequencing [3][4][5] . This is particularly true for Africa, where none of its sequenced indigenous crops were sequenced on the continent 4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, our project provides a model for increasing the representation of local researchers in the sequencing of their indigenous crops. Recent studies and commentaries have highlighted the disconnect between the species origin and the location of the institutions leading their sequencing [3][4][5] . This is particularly true for Africa, where none of its sequenced indigenous crops were sequenced on the continent 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies and commentaries have highlighted the disconnect between the species origin and the location of the institutions leading their sequencing [3][4][5] . This is particularly true for Africa, where none of its sequenced indigenous crops were sequenced on the continent 4 . We surveyed 31 publications describing the genome sequencing of 24 indigenous African crops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New technologies and expanding infrastructure have opened the door for cutting-edge research to be conducted at monumental scales. Despite this noteworthy growth, access to resources is not evenly distributed across the globe and recent studies have revealed striking participation gaps and longstanding disparities tied to colonialism, economic inequality, and systemic biases (Amarante et al 2021; Maas et al 2021; Marks et al 2021; Trisos et al 2021; Ebenezer et al 2022; Topaz et al 2022; Wapman et al 2022). Plant science, in particular, suffers from more acute historical exclusion and ongoing underrepresentation of marginalized identities compared to other biological disciplines (Madzima and MacIntosh, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Global economic disparities, established under imperial colonialism and perpetuated through modern eurocentric frameworks, further exacerbate underrepresentation of diverse perspectives in plant science (Baber 2016; Li 2021; Marks et al 2021). Researchers working in low-income countries and under-resourced institutions face multiple barriers to participating in plant science research, including limited funding opportunities, reduced access to cutting-edge technologies and infrastructure, and exclusion from collaboration networks (Ebenezer et al, 2022; Ibe, 2022). In the field of plant genomics for instance, few projects have been led by researchers in the Global South, despite the striking biodiversity and extensive local knowledge within these regions (Marks et al, 2021).…”
Section: Introductionmentioning
confidence: 99%